2013
DOI: 10.1016/j.red.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of health insurance reform: Separating regulation from redistribution

Abstract: Two key components of the upcoming health reform in the U.S. are a new regulation of the individual health insurance market and an increase in income redistribution in the economy. Which component contributes more to the welfare outcome of the reform? We address this question by constructing a general equilibrium life cycle model that incorporates both medical expenses and labor income risks. We replicate the key features of the current health insurance system in the U.S. and calibrate the model using the Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 33 publications
(58 reference statements)
3
97
0
Order By: Relevance
“…Several new papers study the importance of medical expense risk in general equilibrium, including Hansen, Hsu, and Lee (2012), Pashchenko and Porapakkarm (2013), and Imrohoroglu and Kitao (2012). Kopecky and Koreshkova (2014) find that old-age medical expenses and the coverage of these expenses provided by Medicaid have large effects on aggregate capital accumulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several new papers study the importance of medical expense risk in general equilibrium, including Hansen, Hsu, and Lee (2012), Pashchenko and Porapakkarm (2013), and Imrohoroglu and Kitao (2012). Kopecky and Koreshkova (2014) find that old-age medical expenses and the coverage of these expenses provided by Medicaid have large effects on aggregate capital accumulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The general results suggest that the health insurance can improve access to hospital, but the impact on OOP health expenditure reduction is paradoxical. For example, for the developed counties in the United States, Canada, Australia and so on, the empirical results indicate that healthcare programme indeed increases healthcare utilization among the poor (Sinclair and Smetters 2004;Goldman et al 2006,Kopecky and Koreshkova 2009,Pashchenko and Porapakkarm 2013, and crowds out medical spending for individuals with low wealth and low health status (Ariizumi 2008), but the OOP spending seems to have increased for the insured in urban areas (Suryahadi 2013). While in developing regions, most of the studies concluded the increasing coverage of health insurance has also increased hospital utilization (Cheng and Chiang 1997;Chen et al 2007) and lowered outpatient and inpatient treatment costs in Vietnam and Mexico (Wagstaff and Pradhan 2006;Galárraga et al 2010), particularly for the low-income households (Sheu and Lu 2014), However, Wagstaff (2010) found no impact of Vietnam's recent healthcare fund for the poor and on hospital utilization, although it does seem to have reduced OOP health spending.…”
Section: Impact Of Healthcare On Medical Expenditurementioning
confidence: 99%
“…The Cobb-Douglas function parameter α is set at 0.33, which corresponds to the 11 More details are available in Pashchenko and Porapakkarm (2013b). 12 Given that we have indivisible labor supply we cannot pin down this parameter using a moment in the data.…”
Section: Demographics Preferences and Technologymentioning
confidence: 99%